Caring alone: older adult care burdens, practices, and structural imbalances among China’s one-child generation - Xiang, Shuai; Xiang, Hongxu; Ren, Qiao; Deng, Qinwen (Frontiers in Public Health, 2025)
BackgroundBetween 1980 and 2015, China’s one-child policy reshaped family structures. Now, as this generation enters adulthood and their parents age, the only children face the daunting challenge of supporting multiple older parents in an increasingly aging society.PurposeThis study focuses on the practical challenges and needs faced by China’s one-child generation in caring for their aging parents. By examining their caregiving experiences, the study aims to reveal the multiple pressures they bear and to provide policy- and system-level insights for alleviating the older adult care burden on this unique generation.MethodThis study is a qualitative analysis based on content from social media. A grounded theory analysis of online discussions was conducted using NVivo 14.0 (QSR International). Focusing on questions such as “What happens as the parents of one-child families grow old, and who will ensure their care?,” our study systematically gathered and coded discussions from Zhihu, a major social media platform in China.ResultsThe Chinese only children in this study’s sample face intense older adult care pressure, including economic strain, labor shortages, and emotional exhaustion. They struggle to balance caregiving with career development while shouldering dual pressures of supporting both aging parents and young children. Structural inequalities—such as the gap between government promises and actual social security, and disparities between urban and rural areas, as well as within and outside the formal system—worsen the challenge. At the same time, the weakening of traditional filial piety deepens cultural and psychological strains, further fragmenting intergenerational caregiving responsibilities.DiscussionResearch indicates that the issue of older adult care for parents of only children in the sample requires not only the reconstruction of a fairer and more sustainable older adult care ethic across society but also urgent institutional efforts to promote more inclusive and equitable support for older adult care and medical services. Meanwhile, the sample observations indicate that the development of technology and the establishment of a high-quality, affordable older adult care service system will become important pathways to easing the caregiving pressure of the one-child generation and providing greater social support.